Pengaruh Persepsi Manfaat Dan Kepercayaan Terhadap Minat Beli Cryptocurrency Di Kalangan Mahasiswa Bina Sarana Informatika Margonda - Willyan Muslim; Ratnawaty Marginingsih (Jurnal Transformasi Bisnis Digital, 2025)
Cryptocurrency has become a new trend in the world of digital finance, but its adoption is still limited among the public. This study aims to analyze the effect of perceived benefits and trust on cryptocurrency purchase intention among students of Bina Sarana Informatika Margonda University. A quantitative approach was used by distributing questionnaires to student respondents. Data processing uses the SPSS 25 application and data analysis is carried out by testing validity, reliability, classical assumptions, multiple linear regression, hypothesis testing and the coefficient of determination. The results showed that partially perceived benefits had no effect, while trust was proven to have an influence. Simultaneously, perceived benefits and trust affect cryptocurrency purchase intention. The findings imply the importance of increasing understanding of the benefits and building public trust, especially students, in cryptocurrency to encourage the adoption of this technology. This research also highlights the need for further education on the potential and risks of cryptocurrencies, as well as the development of supportive regulations to increase trust and adoption among students and the general public